Evaluation of the first 5 years of a glutaric aciduria type I neonatal screening programme in Asturias - Ana Isabel Elola Pastor; Belén Prieto García; Juan José Díaz Martín (Elsevier, 2024)
Introduction: . Neonatal screening of glutaric aciduria type 1 (GA-1) has brought radical changes in the course and outcomes of this disease. This study analyses the outcomes of the first 5 years (2015-2019) of the AGA1 neonatal screening programme in our autonomous community. Material: . We conducted an observational, descriptive and retrospective study. All neonates born between January 1, 2015 and December 31, 2019 that participated in the neonatal screening programme were included in the study. The glutarylcarnitine (C5DC) concentration in dry blood spot samples was measured by means of tandem mass spectrometry applying a cut-off point of 0.25 µmol/L. Results: . A total of 30 120 newborns underwent screening. We found differences in the C5DC concentration based on gestational age, type of feeding and hours of life at sample collection. These differences were not relevant for screening purposes. There were no differences between neonates with weights smaller and greater than 1500 g. Screening identified 2 affected patients and there were 3 false positives. There were no false negatives. The diagnosis was confirmed by genetic testing. Patients have been in treatment since diagnosis and have not developed encephalopathic crises in the first 4 years of life. Conclusions: . Screening allowed early diagnosis of two cases of GA-1 in the first 5 years since its introduction in our autonomous community. Although there were differences in C5DC levels based on gestational age, type of feeding and hours of life at blood extraction, they were not relevant for screening. Resumen: Introducción: El cribado neonatal de la aciduria glutárica tipo 1(AG-1) ha supuesto un cambio radical en la evolución y debut de la enfermedad. En este estudio se analizan los resultados de los primeros cinco años (2015-2019) del programa de cribado neonatal (PCN) de AG-1 en nuestra comunidad. Material: Se diseñó un estudio observacional, descriptivo y retrospectivo. La población estaba formada por neonatos participantes en el PCN nacidos entre el 1 de enero de 2015 y el 31 de diciembre de 2019. La determinación de glutarilcarnitina (C5DC) en sangre impregnada en papel se realizó mediante espectrometría de masas en tándem con punto de corte en 0,25 µmol/L. Resultados: El cribado se llevó a cabo en 30120 recién nacidos. En el análisis del marcador C5DC se encontraron diferencias en la concentración dependiendo de la edad gestacional, del tipo de alimentación y de las horas de vida a la extracción. Estas diferencias no fueron relevantes a efectos del cribado. No se observaron diferencias entre menores y mayores de 1500 g. Se identificaron 2 casos afectos y 3 falsos positivos. No se detectaron falsos negativos. Los diagnósticos fueron confirmados mediante estudio genético. Los pacientes reciben tratamiento desde el diagnóstico y no han presentado crisis encefalopáticas los primeros cuatro años de vida. Conclusiones: El cribado ha permitido el diagnóstico precoz de dos casos de AG-1 en los cinco primeros años desde su instauración en nuestra comunidad. Aunque existen diferencias en los niveles de C5DC en función de edad gestacional, del tipo de alimentación y de las horas de vida a la extracción, estas no tuvieron trascendencia para el cribado.